2019
DOI: 10.1159/000497482
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Postoperative Antibiotics for Patients with a Complex Appendicitis

Abstract: Postoperative antibiotics are recommended after appendectomy for complex appendicitis to reduce infectious complications. The duration of this treatment varies considerably between and even within institutions. The aim of this review was to critically appraise studies on duration of antibiotic treatment following appendectomy for complex appendicitis. A systematic literature search according to the PRISMA guidelines was performed. Comparative studies evaluating different durations of postoperative antibiotic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The meta-analysis by Van den Boom et al, including nine studies with more than 2,000 patients with complicated AA, revealed a statistically significant difference in IAA incidence between the antibiotic treatment of ≤ 5 vs > 5 days (OR 0.36), but not between ≤ 3 vs > 3 days (OR 0.81) [224].…”
Section: Q47: Does Aspiration Alone Confer Clinical Advantages Overmentioning
confidence: 99%
“…The meta-analysis by Van den Boom et al, including nine studies with more than 2,000 patients with complicated AA, revealed a statistically significant difference in IAA incidence between the antibiotic treatment of ≤ 5 vs > 5 days (OR 0.36), but not between ≤ 3 vs > 3 days (OR 0.81) [224].…”
Section: Q47: Does Aspiration Alone Confer Clinical Advantages Overmentioning
confidence: 99%
“…In patients with intra-abdominal infections who had undergone an adequate source control, the outcomes after fixed-duration antibiotic therapy (approximately 3-5 days) are similar to those after a longer course of antibiotics. The meta-analysis by Van den Boom et al, including nine studies with more than 2,000 patients with complicated appendicitis, revealed a statistically significant difference in incidence between the antibiotic treatment of ≤5 vs. > 5 days, but not between ≤3 vs. > 3 days [54,55].…”
Section: Postoperative Antibiotic Therapymentioning
confidence: 99%
“…The meta-analysis by Van den Boom et al, including nine studies with more than 2,000 patients with complicated AA, revealed a statistically significant difference in IAA incidence between the antibiotic treatment of ≤5 vs >5 days (OR 0.36), but not between ≤3 vs >3 days (OR 0.81) [224]. A total of 80 patients were enrolled in a recent RCT comparing the outcomes of short (24 h) and the extended (>24 h) postoperative antibiotic therapy in complicated AA.…”
Section: Q72: Are Postoperative Antibiotics Always Indicated In Adult Patients Following Appendectomy?mentioning
confidence: 99%